Models of sumultaneity and sequentiality in human cognition - Durbin, Marshall (The Peter de ridder, 1975)
One of the goals of social science has been to seek models which adequately represent the organizin principle of human behavior. In this paper, I would like to discuss this search for models from the standpoint of the sequential organization vs. the simultaneous organization of behavior.